Biological security education, awareness, and outreach as essential elements of strengthening the review of science and technology under the BTWC - Novossiolova, Tatyana; Shang, Lijun; Dando, Malcolm (2022)
A slideshow of a talk given about the biological security education, awareness, and outreach as essential elements of strengthening the review of science and technology under the BTWC, held on the 6th April 2022.